2014
DOI: 10.1523/jneurosci.5454-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Rebound Potentiation of Inhibition in Juvenile Visual Cortex Requires Vision-Induced BDNF Expression

Abstract: The developmental increase in the strength of inhibitory synaptic circuits defines the time window of the critical period for plasticity in sensory cortices. Conceptually, plasticity of inhibitory synapses is an attractive mechanism to allow for homeostatic adaptation to the sensory environment. However, a brief duration of visual deprivation that causes maximal change in excitatory synapses produces minimal change in inhibitory synaptic transmission. Here we examined developmental and experience-dependent cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 38 publications
2
33
1
Order By: Relevance
“…The only effect on the amplitude of mIPSCs was observed when DE mice were re-exposed to light during the critical period, which we recently reported as a novel form of rebound potentiation of inhibition that depends on rapid transcription of brain-derived neurotrophic factor [37]. Our data indicate that the regulation of mIPSC amplitude and frequency can occur independently of each other, and that visual experience specifically controls mIPSC frequency in adults.…”
Section: Results (A) Visual Experience Exclusively Regulates Miniatursupporting
confidence: 49%
See 1 more Smart Citation
“…The only effect on the amplitude of mIPSCs was observed when DE mice were re-exposed to light during the critical period, which we recently reported as a novel form of rebound potentiation of inhibition that depends on rapid transcription of brain-derived neurotrophic factor [37]. Our data indicate that the regulation of mIPSC amplitude and frequency can occur independently of each other, and that visual experience specifically controls mIPSC frequency in adults.…”
Section: Results (A) Visual Experience Exclusively Regulates Miniatursupporting
confidence: 49%
“…We recently reported that once the developmental switch in GABA A R properties occurs the receptors are no longer regulated by neural activity [37] (electronic supplementary material, figure S1). At the age when postsynaptic GABA A Rs are malleable, changes occurred through altering the number of receptors rather than their conductance [37] (electronic supplementary material, figure S1c,d). This is also seen from in vitro studies [51,52], suggesting that the main postsynaptic mode of inhibitory synapse regulation is via controlling the number of GABA A Rs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous efforts to understand the functional significance of individual transcripts focused exclusively on promoter IV because of its established role in activity-dependent transcription (Gao et al, 2014;Hong et al, 2008;Martinowich et al, 2011;Sakata et al, 2013;Sakata et al, 2009). These studies determined that loss of BDNF expression from promoter IV is sufficient to generate specific behavioral and cellular effects, but whether loss from other Bdnf promoters caused similar impairments was not studied (Gao et al, 2014;Hong et al, 2008;Martinowich et al, 2011;Sakata et al, 2013;Sakata et al, 2009). To address the outstanding question of whether BDNF produced from different promoters governs discrete molecular, cellular, and behavioral functions, we generated a novel set of transgenic mice in which BDNF production from promoters I, II, IV, or VI is selectively disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a selective deletion of BDNF exons I-III that spares the remaining portion of the gene is sufficient to cause obesity in humans (Han et al, 2008). In mice, selective BDNF disruption from promoter IV, which significantly contributes to activity-dependent BDNF production, leads to impaired GABAergic transmission and behavioral perseverance (Gao et al, 2014;Hong et al, 2008;Martinowich et al, 2011;Sakata et al, 2013;Sakata et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…bicucullin or picrotoxin), decreases AMPA receptor content resulting in inhibition of synaptic strength. In in vivo system, depriving sensory input such as vision, scales up excitatory synapses in the visual cortex and, reexposing the visually deprived animals to light results in scaling down of synaptic strength (512). This sensory experience dependent synaptic scaling is mainly considered to be postsynaptic in nature at the level of AMPA receptor expression and activation globally or at individual synapses (3;13).…”
Section: Introductionmentioning
confidence: 99%